Supporting and Inhibiting Factors in the Implementation of Inter-professional Collaboration in Nursing - I Ketut Astawa; NLP Dina Susanti; Ni Luh Dwi Indrayani; Made Dian Shanti Kusuma (GLOBAL HEALTH SCIENCE GROUP, 2026)
Inter-professional collaboration has a positive impact on patient outcomes and enhances job satisfaction. However, its implementation faces numerous challenges. To date, no literature review has systematically summarized the factors influencing nurses' participation in collaborative practice. This literature review aims to systematically summarize the factors affecting the implementation of inter-professional collaboration (IPC) among nurses. This scoping review adopts the PCC (Population, Content, Context) approach, where the population consists of nurses, the content focuses on inter-professional collaboration, and the context is hospital settings. Article searches were conducted in two databases, PubMed and Science Direct, covering the period from 2020 to 2025, using keywords: “inter-professional collaboration” AND “nurse” AND “hospital” AND “factor.” The search yielded 727 articles, with 15 included in the review. Eligible full text articles underwent critical appraisal, followed by data extraction, including details such as author names, publication year, country, title, objectives, research methods, findings, and research gaps the supporting factors for IPC implementation by nurses include effective communication practices, enhanced collaborative competencies, and the implementation of inter-professional education. Conversely, the barriers to IPC implementation by nurses involve unclear role definitions, poor organizational management, weak leadership, as well as high stress and workload. These findings highlight the numerous challenges in IPC implementation among nurses. The development and implementation of policies that support IPC are crucial.